NEW FOSSIL REMAINS OF BRACHYPOTHERIUM PERIMENSE FROM THE CHINJI AND NAGRI FORMATIONS OF PAKISTAN - A. M. Khan; M. Akhtar; M. A. Khan; A. Shaheen (Journal of Animal and Plant Sciences, 2012)
Brachypotherium perimense is a well known extinct species of family Rhinocerotidae from the Siwaliks of Pakistan. The specimens described in this paper were collected during field work from the Late Miocene localities of the Chinji and Nagri formations in district Chakwal, Punjab, Pakistan. Based upon the morphological and metric similarities the specimens are assigned to Brachypotherium perimense (Falconer and Cautley, 1847).
Keywords: Teleoceratini; Rhinocerotidae; Mammals; Siwaliks; Miocene.